Seismic Performance Evaluation of Intermediate Moment Frames with Reduced Beam Section and Bolted Web Connections. Issue 2 (May 2015) - Han, Sang Whan; Moon, Ki Hoon; Hwang, Seong-Hoon; Stojadinovic, Bozidar
A reduced beam section with a bolted web (RBS-B) connection is permitted for use only in intermediate moment frames (IMF) according to the ANSI/AISC 358-05 . This is because some RBS-B test specimens failed to achieve 4% total rotation capacity, which is the minimum story drift angle required for special moment frames (SMF). Several studies reported that some RBS-B connections could experience brittle connection fracture during earthquakes, which can also be detrimental to the seismic performance of IMF systems with RBS-B connections. For investigating whether IMFs with RBS-B connections provide a satisfactory seismic performance, this study evaluated the seismic performance of IMFs with pre-qualified RBS-B connections following the ATC-63 procedure. Twenty-four model buildings were designed according to current seismic design provisions. Several IMFs with RBS-B connections do not satisfy the acceptance criteria specified in ATC-63 .